Hub-and-spoke maritime network with heterogeneous commodity on island shipping - Adrian Firdaus; Ade Sjafruddin; Russ Bona Frazila; Febri Zukhruf (Journal of International Maritime Safety, Environmental Affairs, and Shipping, 2024)
This paper presents an extension to a classic hub-and-spoke maritime network, by adding the feeder node and heterogeneous commodity to the network on an island shipping network. The cargo is delivered from origin (hub) to destination (feeder), which can be compounded in hub node and sent using container in container ship to a spoke node. In the spoke node, the container is de-containerized into general cargo package, representing heterogeneous commodity, and finally shipped using cargo ship to the feeder node. This system is suitable for island shipping network, consisting of several small ports with marginal hinterland, where the development of container facility is not financially feasible. The proposed model generates the optimum number and location of spoke, alongside with its allocated feeder node, to minimize the total shipping cost. As a case study, an actual island network in Southeast Sulawesi, Indonesia, is utilized, resulting in a recommendation of one additional spoke to the existing network. The result also suggests a backup spoke if the single spoke scheme is selected, anticipating any disruption on the selected spoke node. A trade-off between shipping cost reduction and spoke investment cost should be considered by policymakers in the adoption of the system.